Psycholinguistic Studies in Second Language Acquisition from the Environment in Toddlers - Baraba, Afnan (Proceedings of International Conference on Islamic Civilization and Humanities, 2023)
Language is the ability to communicate among individuals in carrying out their activities. Language can be acquired by individuals in two ways: (1) first language acquisition, commonly known as the mother tongue, and (2) second language acquisition. The ways of language acquisition in communication fall under the field of Psycholinguistics. To better understand the process of language acquisition, we can delve into psycholinguistics. This research aims to discuss the influence of the environment on second language acquisition in toddlers. The method used by the author in this study is qualitative descriptive.